The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/md.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Peripheral Arterial Disease After Hip Replacement

Abstract: The correlation between hip replacement (Hip-Rep) and peripheral arterial disease (PAD) remains uncertain. Thus, we investigated the relationship between Hip-Rep and risk of developing PAD in a nationwide retrospective cohort study.National Health Insurance data were used to assemble a cohort of patients who were diagnosed from 2000 to 2011. Patients with a history of PAD were excluded. A total of 5284 patients who received a Hip-Rep and 21,124 matched controls were enrolled. We used Cox proportional hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Though our results are statistically significant, other literature supporting this is lacking. Furthermore, as shown in previous research, a greater risk seems to be shown at 1 year revision than at 5 years [38], which contradicts the findings of this study. Concerning the lesser represented comorbidities, in THA there is a slight possibility of a relationship between increased risk of revision and metastatic cancer in the short-term, and psychoses in the medium-term, which has also been found in previous studies [13].…”
Section: Discussioncontrasting
confidence: 88%
“…Though our results are statistically significant, other literature supporting this is lacking. Furthermore, as shown in previous research, a greater risk seems to be shown at 1 year revision than at 5 years [38], which contradicts the findings of this study. Concerning the lesser represented comorbidities, in THA there is a slight possibility of a relationship between increased risk of revision and metastatic cancer in the short-term, and psychoses in the medium-term, which has also been found in previous studies [13].…”
Section: Discussioncontrasting
confidence: 88%
“…Hip arthroplasty has, however, been associated to peripheral arterial disease at long-term follow up. 21 This study was performed in China which implies that the association between total hip arthroplasty and vascular disease may be generalized to different regions of the world. The generalizability of the results on a global scale is further supported by the fact that the Swedish hip arthroplasty cohort differs marginally when compared with other large joint arthroplasty cohorts in the Nordic countries 22 24 as well as in England, 25 Australia, 26 New Zeeland, 27 and United States.…”
Section: Discussionmentioning
confidence: 99%
“…***p< 0.001. afterward. RA is a systemic inflammatory disease, with early stages of the disease leading to atherosclerotic changes (4,29,30). Georgiadis et al suggested that atherosclerotic changes in patients with RA improved after a one-year treatment of disease-modifying antirheumatic drugs (31).…”
Section: Discussionmentioning
confidence: 99%
“…If these doctors or hospitals make wrong diagnoses or coding, they will be punished with a lot of penalties. Therefore, the diagnoses and codes for acute pancreatitis and PAOD used in this study should be correct and reliable (27)(28)(29).…”
Section: Study Patientsmentioning
confidence: 99%